Technology-Based Islamic Religious Education Policy: a Regulatory Study af Madrasahs and Schools in Indonesia - Hengki Satrisno; Alfauzan Amin; Zubaedi Zubaedi; Rohimin Rohimin; Wildan Nur Hidayat (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2026)
This study examines the regulatory framework and implementation of technology-based Islamic Religious Education (IRE) policies in madrasahs and schools in Indonesia. A qualitative approach with a normative–empirical design is employed to analyze policy documents, educational regulations, and relevant scholarly literature. Findings indicate that government policies have increasingly emphasized digital transformation, integration of information and communication technology, and the development of teacher digital competencies within Islamic education. Regulatory structures demonstrate a dual governance system between madrasahs and general schools, which influences policy interpretation and implementation across institutions. Implementation challenges include disparities in infrastructure, limited digital readiness among educators, and inconsistencies in curriculum adaptation. Policy gaps are also identified in coordination between governing bodies and in the operationalization of digital governance systems. Effective implementation requires stronger institutional support, capacity building, and alignment between technological innovation and Islamic educational values. The study concludes that technology-based IRE policy plays a strategic role in enhancing educational quality, but its success depends on comprehensive, adaptive, and context-sensitive regulatory frameworks.